Desain Dakwah Untuk Pembinaan Keagamaan Komunitas Elit Intelektual - Bukhari Bukhari (Universitas Islam Negeri Mataram, 2008)
Dakwah must be designed dynamically to be able to respond various problems. One of dakwah objects that should be specifically considered is intellectual community. They are educated people who are used to think critically, objectively and systematically. They prioritize brain works over muscle ones. To face them we need to prepare special dakwah approaches that move and lead their mind and direct their contaminated ideas, and dakwah subjects that are suitable to their intelligence and religious understanding. To meet such requirements, dakwah institutions should recruit preachers whose excellent capabilities of academic and social aspects. With academic capabilities, preachers can deliver dakwah by logic methods. In addition, they can construct dakwah materials based on logical arguments. With social capabilities, preachers find it easier to know dakwah objects’ characteristics. Therefore, preachers do not find any obstacle to enter into intellectual communities as their dakwah objects.